Reproduction, discipline, inequality: Critiquing East-Asian developmentalism through a strategic-relational examination of Singapore's Central Provident Fund. (December 2022) - Greener, Joe; Yeo, Eve
The five 'developmentalist' welfare states of East Asia (South Korea, Singapore, Taiwan, Hong Kong and Japan) have been presented as successful projects of economic progress, positively aligning citizen-interests with business objective. Utilising Jessop's Strategic-Relational Approach (SRA), we analyse the Central Provident Fund (CPF), Singapore's 'forced savings' social policy which organises housing, healthcare, education and retirement. Through a myriad of eligibilities/ineligibilities, Singapore's CPF administers desired social behaviours while sustaining a series of inequalities supporting certain classed and gendered interests over others. Our analysis breaks down the CPF into three social relational orientations: (1) heteronormative familial responsiblisation, (2) labour market activation and (3) class reproduction. The article highlights the function of CPF in institutionalising conservative and pro-market political interests. CPF reproduces material inequalities and fashions behaviours conducive with the dominant accumulation strategy while discouraging those which are not, privileging some interests over others.